Analisis Faktor Penyerapan Tenaga Kerja Di Jawa Tengah - Shinta, Aulia Isna (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Timor, 2024)
Abstract. This study examines the effects of economic development, minimum wage, and educational attainment on labour absorption across all Indonesian provinces. Utilising a quantitative methodology, secondary data sources are sourced from the website of the Central Java Provincial Statistics Agency.The research employed a sample derived from the districts and cities situated in the Indonesian province of Central Java. The analysis of the data was done with Eviews version 12. The analysis of the data reveals that while the minimum wage and economic growth have positive and substantial effects on labour absorption, education level has a negative and significant impact on it. Keywords: Education Level; Minimum Wage; Economic Growth; and Labor Absorption.